A importância dos gêneros textuais no processo de ensino e aprendizagem de alunos surdos - CUIMAR, Osmael Pantoja (2019)
This article aims to emphasize the relevance of textual genres as a methodology in the education process of deaf students. This work was developed from a qualitative perspective, with field research and data gathering, developed through observation, interaction, half-directed interviews, bibliography and activities with two sixth year's deaf students from Igarapé-Miri's fundamental school, located in Pará state. This study arose from a methodologial need with differentiated strategies according to the student's previous knowledge. At first, the research was based on the regular class activities observations, i. e., without a specific methodology, as an evaluation method of their portuguese learning as a second language (L2) in writing modality. Afterward, with activities formutalion, using textual genres, as for instance, videos, images, newspapers, letters and e-mails, as a teaching and learning methodology, having the comparison and evaluation of the students as a perspective, to, therefore, understand the efficiency and relevance of this method to deaf students education. The result shows that, without a specific methodology, the learning of L2 is very hard, thus, deaf students need activities prepared accordinly to their daily life, and using these resources, they can read and write with complete understanding, to, therefore, apply their citizenship at the world where they live.